Implementation Of Historical Approach And Philosophical Approach In Learning Al-Qur'an Hadith At MAS Al-Khairiyah - Bahyati, Bahyati; Ranuwijaya, Utang; Muhajir, Muhajir; Inayah, Bidayatul (Arfannur, 2024)
This research aims to find out the historical and philosophical perspectives in learning Al-Qur'an Hadith. Learning the Qur'an and Hadith is a type of educational endeavor that includes studying the texts, as well as their philosophical and historical context. In everyday life, there are still many Muslims and Muslim women who do not know what is involved in the historical and philosophical approach to studying Al-Qur'an Hadith. This research method is qualitative research which includes field research, using descriptive information in the form of written or spoken words from people and attitudes that can be observed. This research was carried out at MAS Al-Khairiyah Citangkil. The results of this research can be concluded that the historical approach in studying the Al-Qur'an and other historical sources is a systematic study that collects knowledge about the past.